Geotechnical Properties of Bauxite: A Case Study in Bukit Goh, Kuantan, Malaysia. Issue 1 (December 2021) - Hasan, M; Zaini, M S I; Zulkafli, A S; Wahab, A; Hokabi, A A; Masri, K A; Jaya, R P; Hyodo, M; Winter, M J; Sholichin, M; Haribowo, R; Zulkafli, M S
Abstract: The research focuses on the basic and morphological characteristics to ensure bauxite ore reached the International Maritime Solid Bulk Cargoes Code (IMSBC Code) standard before being exported to other countries. The testing procedure, referred to as Geo-spec 3: Model Specification for Soil Testing, was performed to discover the basic parameters of the soil, including pore size distribution, water content, particle density, and morphology qualities. At Bukit Goh, Kuantan, about four (4) samples were chosen, whereas two (2) samples were from the stockpile and two (2) samples were from the Bukit Goh mine. The results illustrated that the mean water content of the soil is 20.64% which is above 10% of the recommended value. The value of Bulk Density is not in the range of 1190 kg/m 3 to 1389 kg/m 3, which is 2836.25 kg/m 3 and the particle size distribution for fine material is greater than 30%, and coarse material is less than 70%. The SEM examination revealed a high concentration of tiny particles in bauxite samples. Bukit Goh bauxite cannot be classified as group C under the IMSBC Code. As a result, the bauxite does not meet the criteria and cannot be shipped.